Guidelines for Developing the Learning Process of Empathy Card for Patients and Caregivers in the Context of Thai Society - Anuraktham, Patiphat; Kanjanaphitsarn, Supre (Asia Social Issues, 2025)
The Empathy card for Patients and Caregivers, known as the Rainy Card, was meticulously crafted by Peaceful Death, and it holds a significant place in the context of Thai Society. This tool is used for listening and caring for patients and caregivers, and its detailed steps were designed for organizing one-on-one learning. This study was qualitative research based on phenomenological methodology, aimed to investigate the attitudes of facilitators, patients, and caregivers based on direct Rainy Card learning experiences and investigate the guidelines for improving the Rainy Card learning process for mental health care of patients and caregivers in the Thai context. The primary data collection was an in-depth interview. There were 47 participants, including 21 facilitators, 10 patients, and 16 caregivers, all with experience in the Rainy Card learning process. The results of the study have been summarized to illustrate the benefits of the card, including: 1) Being listened to gives a pleasant sensation, 2) Accepting the truth, 3) Self-understanding, 4) Understanding others, 5) Daily life and relationships with others. Furthermore, the findings in developing guidelines for organizing the learning process revealed important skills for the Rainy Card learning process, as follows: 1) Listening skills, 2) Interaction with service recipients, 3) Procedures to organize the process, 4) Deep self-observation, 5) Utilizing different tools to organize the learning process, 6) Group learning process. In addition, the research team presented basic concepts for implementing the Rainy Card learning process in the organization of a learning process, including obstacles, precautions, and recommendations for its improvement.